Education for civic and political participation : a critical approach - Hedtke, Reinhold; Zimenkova, Tatjana (New York : Routledge, 2013)
'Participation as an element of active citizenship in democracies is a key project of international and national educational policy. Institutionalized approaches for compulsory schools provide participatory access to all young European citizens. But does this picture depict the possibilities and practices of participation appropriately? Can this standard approach to participation be translated into action in view of diverse polities, policies, political cultures, institutions and practices of participation? This book explores what prerequisites must be given for a successful implementation of such a comprehensive international project'--
Includes bibliographical references (p. [239]-266) and index.
Keywords: Citizenship -- Study and teaching -- Europe -- Cross-cultural studies; Democracy and education -- Europe -- Cross-cultural studies